2023
DOI: 10.3390/genes14040841
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing in Hypoxia-Adapted T98G Glioblastoma Cells Provides Supportive Evidence for IRE1 as a Potential Therapeutic Target

Abstract: Glioblastoma (GBM) is an aggressive brain cancer with a median survival time of 14.6 months after diagnosis. GBM cells have altered metabolism and exhibit the Warburg effect, preferentially producing lactate under aerobic conditions. After standard-of-care treatment for GBM, there is an almost 100% recurrence rate. Hypoxia-adapted, treatment-resistant GBM stem-like cells are thought to drive this high recurrence rate. We used human T98G GBM cells as a model to identify differential gene expression induced by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…S9 ). In literature, a recent study in the same cell line reported a substantial number of DEGs following the 72-h hypoxia treatment of passage number 3 cells, with upregulation of the Warburg effect-related genes such as inositol-requiring enzyme 1 ( IRE1 ) or lactate dehydrogenase A ( LDHA ) 56 . Neither IRE1 nor LDHA were identified as DEGs in our study, which may be explained by the shorter treatment times and higher cell passage number in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…S9 ). In literature, a recent study in the same cell line reported a substantial number of DEGs following the 72-h hypoxia treatment of passage number 3 cells, with upregulation of the Warburg effect-related genes such as inositol-requiring enzyme 1 ( IRE1 ) or lactate dehydrogenase A ( LDHA ) 56 . Neither IRE1 nor LDHA were identified as DEGs in our study, which may be explained by the shorter treatment times and higher cell passage number in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The moderate effect of hypoxic treatment on the gene transcription in the DMSO-treated T98-G cells confirmed this notion (Figure 4). In literature, a recent study in the same cell line reported a substantial number of DEGs following the 72-h hypoxia treatment of passage number 3 cells, with upregulation of the Warburg effect-related genes such as inositol-requiring enzyme 1 (IRE1) or lactate dehydrogenase A (LDHA) 30 . Neither IRE1 nor LDHA were identified as DEGs in our study, which may be explained by the shorter treatment times and higher cell passage number in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“… 69 White et al. 70 found that IRE1 was among the highest hypoxia DEGs in the T98G cell line and had a key role in the neovascularization and invasiveness of GB. The modulation of TME is essential for GB progression.…”
Section: Unfolded Protein Response In Glioblastoma Pathophysiologymentioning
confidence: 99%
“…The preceding led to reduced tumor growth, invasiveness and decreased angiogenesis, and blood perfusion with increased overall survival in xenograph mice. 69 White et al 70 found that IRE1 was among the highest hypoxia DEGs in the T98G cell line and had a key role in the neovascularization and invasiveness of GB. The modulation of TME is essential for GB progression.…”
Section: Angiogenesis Invasiveness and Tme Modulation In Gbmentioning
confidence: 99%